Variations of celiac axis, common hepatic artery and its branches in 600 patients - Sureka, Binit; Mittal, Mahesh Kumar; Mittal, Aliza; Sinha, Mukul; Bhambri, Narendra Kumar; Thukral, Brij Bhushan (Indian Journal of Radiology and Imaging, 2013)
Purpose: To evaluate the spectrum of celiac axis, common hepatic artery (CHA), right, left, middle hepatic artery and gastroduodenal artery variations by using spiral computed tomography (CT). Materials and Methods: A retrospective review of Multidetector CT (MDCT) abdominal angiography scans was performed in patients sent for various liver and other abdominal pathologies between January 2012 and February 2013. A total of 600 patients were evaluated. Definitions of CHA, ambiguous celiac axis, course and division patterns of CHA, replaced hepatic artery, accessory hepatic artery and middle hepatic artery were used as proposed by Song et al., Covey et al., and Wang et al. The pattern of the aortic origin of branches of celiac axis, common hepatic artery and its branches was analyzed. Results: Six types of celiac axis anatomic variations were identified in our study. A total of 546 of the 600 patients had a normal celiac axis anatomy. Anatomic variations were seen in 5.5% of patients. Ambiguous anatomy was seen in 3.5% of the patients. CHA originated from celiac axis in 95.83% of the patients. Variations in anatomic origin of CHA were seen in 8 patients. Ambiguous dual pathway was seen in 4 patients. Normal Sp-preportal course of CHA was identified in 97.78% of cases, Sp-retroportal course in 7 patients, Tp-preportal course in 2, Tp-retroportal in 1, Ip-preportal in 1 and through Ligamentum venosum in 2 patients. Normal origin of RHA from HAP was seen in 79.6% patients. Replaced origin of RHA was seen in 15.16% cases and Accessory origin of RHA was seen in 5.16% cases. LHA originated from HAP in 81.5% patients. Replaced LHA origin was seen in 10.8% cases and Accessory LHA origin seen in 7.6% cases. MHA originated from RHA in 41.3% patients, LHA in 27.83% and from CHA in 4.5% cases. Origin of MHA could not be defined in 26.3% of patients. GDA originated from CHA in 97.6% of patients, from celiac axis in 1.6%, from RHA in 0.33% in patients. Trifurcation of CHA was seen in 7.16% and quadrifurcation of CHA in 2.16%. Conclusion: CT Angiography is a safe and highly sensitive and accurate modality for evaluation of arterial anatomy and its variants.
Keywords: Abdominal angiography; accessory; ambiguous celiac axis; celiac axis; common hepatic artery; replaced hepatic artery